Corpus-based readability formula for Arabic texts: a prototype - Mat Daud, Nuraihan; Hassan, Haslina; Abdul Aziz, Normaziah (2013)
This research aims to produce a readability formula for Arabic texts. There are already a few formulae used for measuring the readability level of English texts. Among them are Flesch, Gunning Fox and Dale-Chall formulae. Flesch Reading Ease scale is based on sentence length and the number of syllables per hundred words, Gunning Fox Index counts sentence length and percentage of multi-syllabic words and Dale-Chall formula counts sentence length and whether a word appears on a list of acceptable words. However, Arabic has its own language rules. Hence there is a need to develop a readability formula for Arabic. This will greatly assist in the production of texts for comprehension and for testing. A study on readability is therefore crucial in the development of Arabic reading and testing materials and also in language teaching and learning. This paper will present a prototype of a readability formula which is based on word frequency for calculating the level of Arabic texts difficulty.